2006
DOI: 10.1073/pnas.0511287103
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of carbohydrate utilization by Lactobacillus acidophilus using cDNA microarrays

Abstract: The transport and catabolic machinery involved in carbohydrate utilization by Lactobacillus acidophilus was characterized genetically by using whole-genome cDNA microarrays. Global transcriptional profiles were determined for growth on glucose, fructose, sucrose, lactose, galactose, trehalose, raffinose, and fructooligosaccharides. Hybridizations were carried out by using a roundrobin design, and microarray data were analyzed with a two-stage mixed model ANOVA. Differentially expressed genes were visualized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
168
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(188 citation statements)
references
References 54 publications
(62 reference statements)
12
168
0
4
Order By: Relevance
“…No genetic loci involved with carbohydrate metabolism were identified from the list of genes induced by glucose, suggesting that glucose is transported by the constitutively expressed mannose/glucose phospho-enolpyruvate-dependent phosphotransferase system (PEP-PTS) transporter (LBA0452, LBA0454-LBA0456), as suggested previously (26). The transcription analysis indicated that the lac operon in L. acidophilus NCFM is solely responsible for the metabolism of GOS and potentially other lactose-derived galactosides, because the gene induction profile of GOS is comparable to the lactose-induced lac gene expression pattern (26).…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…No genetic loci involved with carbohydrate metabolism were identified from the list of genes induced by glucose, suggesting that glucose is transported by the constitutively expressed mannose/glucose phospho-enolpyruvate-dependent phosphotransferase system (PEP-PTS) transporter (LBA0452, LBA0454-LBA0456), as suggested previously (26). The transcription analysis indicated that the lac operon in L. acidophilus NCFM is solely responsible for the metabolism of GOS and potentially other lactose-derived galactosides, because the gene induction profile of GOS is comparable to the lactose-induced lac gene expression pattern (26).…”
mentioning
confidence: 56%
“…The transcription analysis indicated that the lac operon in L. acidophilus NCFM is solely responsible for the metabolism of GOS and potentially other lactose-derived galactosides, because the gene induction profile of GOS is comparable to the lactose-induced lac gene expression pattern (26). It also indicates that regulation occurs at the transcriptional level, likely depending upon HPr (ptsH, LBA0639), CcpA (ccpA, LBA0431), and HPrK/P (ptsK, LBA0676), all of which are encoded in the L. acidophilus NCFM genome (23) and as previously proposed for carbohydrate utilization in L. acidophilus NCFM (26).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The Bacillus subtilis genome encodes 15 PTS proteins with different sugar specificities (31), one of which is also adjacent to a 1-pfk enzyme. PTS transport systems are linked with uptake of monomeric substrates, whereas ABC transport systems are required for the transport of larger substrates, as shown for L. acidophilus (29). Sucrose-use clusters, including PTSII transporter systems that are up-regulated during growth on sucrose or FOS, have been identified in C. beijerinckii (30), C. acetobutylicum (32), and L. plantarum (23).…”
Section: Discussionmentioning
confidence: 99%
“…2). The gene encoding the fructofuranosidase-linked ABC transport protein was induced strongly during growth on longer-chain inulin substrates, whereas the PTSI had maximum induction on fructose, reflecting the different transport capabilities of these two systems (29).…”
Section: Comparison Of Gene Induction On Different Substrates Using Rmentioning
confidence: 99%